2020
DOI: 10.1101/2020.09.27.315929
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence-dependent mechanics of collagen reflect its structural and functional organization

Abstract: Extracellular matrix mechanics influence diverse cellular functions, yet surprisingly little is known about the mechanical properties of their constituent collagens. In particular, network-forming collagen IV, an integral component of basement membranes, has been far less studied than fibril-forming collagens. A key feature differentiating collagen IV is the presence of interruptions in the triple-helix-defining (Gly-X-Y) sequence along its collagenous domain. Here, we used atomic force microscopy (AFM) to det… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 106 publications
(191 reference statements)
0
10
0
Order By: Relevance
“…To assess performance when tracing experimental images, we compared estimates of persistence lengths of collagen proteins via manual and automated implementations of SmarTrace (6, 7), and also benchmarked by comparing to estimates of DNA’s persistence length on images recorded and analysed by another group (5). These comparisons show the ability of AutoSmarTrace to provide consistent persistence lengths (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To assess performance when tracing experimental images, we compared estimates of persistence lengths of collagen proteins via manual and automated implementations of SmarTrace (6, 7), and also benchmarked by comparing to estimates of DNA’s persistence length on images recorded and analysed by another group (5). These comparisons show the ability of AutoSmarTrace to provide consistent persistence lengths (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy likely arises from the heterogeneous structure of this network-forming collagen, compared with the fibril-forming types I and III collagens. It has been shown that type IV has an inhomogeneous flexibility profile: in particular, the persistence length is significantly lower (∼10 nm) towards the N-terminus of the protein (7, 28). Because of this, and avoidance of chain overlap in chain selection, it may be that more rigid portions of collagen IV chains are retained by the chain selection algorithm, while more flexible regions have a greater likelihood of exclusion from further analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations